Factors affecting stunting among 3–12 years old girls of Purba Medinipur, West Bengal, India - Khanra, Pikli; Chakraborty, Raja; Bose, Kaushik (Anthropological Review, 2023)
Stunting is the impaired growth and development in children caused due to poor nutrition, recurrent infections and lack of psychosocial stimulus. Because stunting affects physical development and inhibits the child from attaining his full cognitive development as an adult, children may never regain the height lost due to stunting. Stunting (Low height-for-age) in infants and young children is a simple, wellknown indicator of undernutrition. The current study sought to determine the effects of socio-economic and demographic factors on the frequency of stunting among Bengalee girls. The study was carried out in the Deshopran block and Haldia municipality area (West Bengal, India). The total number of participants included in the study was 530 Bengalee girls. 53.39% (283) of study participants were urban residents while 46.61% (247) were rural residents. Stunted growth in children was defined as the height for a given age in children less than two standard deviations of the WHO Child Growth Standards. The prevalence of stunting among girls in our study was 11.13%. The predictor variables with substantial associations with stunting in the binary logistic regression (BLR) analyses were further used in the multiple binary logistic regression (MBLR) analyses. Odds ratios with 95% confidence intervals were used to calculate the stunting risk. Results showed that the risk of stunting was significantly associated with low birth weight, presence of younger brothers, a large number of family members and place of delivery. Improving maternal and child access to nutrient-rich food, decreasing infectious disease, and promoting women empowerment initiatives are the main recommendations for resolving the issue.